When are breast cancer patients at highest risk of venous thromboembolism: a cohort study using English healthcare data - Walker, Alex J.; West, Joe; Card, Timothy R.; Crooks, Colin J.; Kirwan, Cliona C.; Grainge, Matthew J. (American Society for Hematology, 2015)
Breast cancer patients are at increased risk of VTE, particularly in the peri-diagnosis period. However, no previous epidemiological studies have investigated the relative impact of breast cancer treatments in a time-dependent manner. We aimed to determine the impact of breast cancer stage, biology and treatment on the absolute and relative risks of VTE, using several recently linked data sources from England. Our cohort comprised 13,202 breast cancer patients from the Clinical Practice Research Datalink (linked to Hospital Episode Statistics and Cancer Registry data), diagnosed between 1997 and 2006 with follow-up continuing to the end of 2010. Cox regression analysis was performed to determine which demographic, treatment-related and biological factors independently affected VTE risk. Women had an annual VTE incidence of 6% whilst receiving chemotherapy which was 10.8-fold higher (95% CI, 8.2 to 14.4; absolute risk (AR) =59.6 per 1000 person-years) than women who did not receive chemotherapy. Following surgery the risk was significantly raised in the first month (HR=2.2; 95% CI 1.4 to 3.4; AR=23.5; reference group, no surgery), but it was not raised subsequent to this. Risk of VTE was noticeably higher in the 3-months following initiation of Tamoxifen compared with the risk before therapy (HR=5.5; 95% CI 2.3 to 12.7; AR=24.1), however commencement of aromatase inhibitors was not associated with VTE (HR=0.8; 95% CI 0.5 to 1.4; AR=28.3). In conclusion, women receiving chemotherapy for breast cancer have a clinically important risk of VTE, whilst an increased risk of VTE immediately following endocrine therapy is restricted to Tamoxifen.